1992
DOI: 10.1136/thx.47.1.14
|View full text |Cite
|
Sign up to set email alerts
|

A 10 year follow up of 180 adults with bronchial asthma: factors important for the decline in lung function.

Abstract: Background Little is known about the factors that determine outcome in asthma. The purpose of this study was to describe the relation of various factors of potential importance to the rate of decline in lung function in adults with intrinsic and extrinsic asthma. Methods Of 180 asthmatic patients, 143 (79%) participated in a 10 year follow up examination. At the time of enrolment all patients underwent certain tests for asthma (case history, total IgE, skinprick tests, the radioallergosorbent test (RAST), hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
79
3
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 17 publications
12
79
3
2
Order By: Relevance
“…For never-smokers aged .50 yrs the annual FEV1 decline has been estimated to be 28 mL in males and 22 mL in females [22], giving a female to male ratio of 0.78, which is approximately the same as the ratio of a female to male 1st percentile FEV1 of 0.8. In patients with asthma, FEV1 decline has been found to be ,50 mL?yr -1 in intrinsic asthmatics and ,23 mL?yr -1 in extrinsic asthmatics [23], and ,32 mL?yr -1 in asthmatic nonsmokers aged 40-60 yrs and ,26 mL?yr -1 in those aged .60 yrs [21]. None of these studies suggested that this loss was a proportional effect.…”
Section: Discussionmentioning
confidence: 98%
“…For never-smokers aged .50 yrs the annual FEV1 decline has been estimated to be 28 mL in males and 22 mL in females [22], giving a female to male ratio of 0.78, which is approximately the same as the ratio of a female to male 1st percentile FEV1 of 0.8. In patients with asthma, FEV1 decline has been found to be ,50 mL?yr -1 in intrinsic asthmatics and ,23 mL?yr -1 in extrinsic asthmatics [23], and ,32 mL?yr -1 in asthmatic nonsmokers aged 40-60 yrs and ,26 mL?yr -1 in those aged .60 yrs [21]. None of these studies suggested that this loss was a proportional effect.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, in several clinic-based studies which evaluated the severity of asthma in relation to age at onset by spirometry, later onset of asthma was a risk factor of persistent airflow limitation [1], low lung function [2] and rapid decline of lung function [3]. In a longitudinal study, airflow limitation and the response to bronchodilator of asthmatics diagnosed at ages of 16-22 years were lower compared with the younger age groups [17].…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinic-based studies have shown that patients with late-onset asthma have persistent airflow limitation [1], low lung function [2] and rapid decline of lung function [3]. In a phenotype classification study [4], late-onset asthma has been associated with less atopy and more severe asthma.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely demonstrated that smoking habits enhance lung function decline in asthmatic subjects (Ulrik et al 1992;Dijkstra et al 2006). In our study, there were no current smokers; however, a signiWcant greater lung function decline was observed in those asthmatic who were exsmokers and who underwent persistent allergen exposure.…”
Section: Discussionmentioning
confidence: 44%